The Transaction of Damaged Cash Exchange in the Perspective of Islamic Economic Law (Case Study in Medan City) - Suhendri Irandi; Mhd Yadi Harahap; Ramadhan Syahmedi Srg (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
From the discussion of damaged cash exchange transactions carried out by corrupted money collectors in the city of Medan, the author can draw several conclusions, as follows: Currency transactions that are unfit for circulation that occur in the city of Medan are closely related to the concept of the sharf contract in the perspective of Islamic economic law. This is, if we look at it from the object being transacted, namely currency, even though the money is money which is not fit for circulation. In this transaction, the terms and conditions in the sharf contract concept must be fulfilled in it. The application of Law of the Republic of Indonesia Number 7 of 2011 concerning Money Changes in the community has been running, but is still not optimal. This is because there are still many people who do not know or do not understand how to exchange their damaged cash. Most people feel that the damaged cash they have is no longer sold to be spent. In fact, based on the Regulation of Members of the Board of Governors Number 19/13 / PDADG / 2017 concerning Rupiah Currency Exchange, it explains the procedure for exchanging money that is not fit for circulation. In the perspective of Islamic economic law, the practice of changing corrupted money by the corrupt money-seeking community is divided into three opinions. One opinion says, it is legally forbidden'. This opinion argues that the laws that apply to paper money also apply to gold and silver. There are two requirements in the sale and purchase of gold with gold or silver and silver, namely: the same weights and cash in one agreement. Meanwhile, the second opinion is allowed even though there is a difference in the nominal value. Another case is the third opinion which first sees the public's attitude towards money unfit for circulation.